Trends of Medicare Reimbursement Rates for Lower Extremity Procedures - Siotos, Charalampos; Aminzada, Amir; Whitney, Natalia; Najafali, Daniel; Toms III, John A.; Mpontozis, Anastasios; Kokosis, George; Shenaq, Deana S.; Derman, Gordon H.; Dorafshar, Amir H.; Kurlander, David E. (Journal of Reconstructive Microsurgery, 2023)
Background Data collected across many surgical specialties suggest that Medicare reimbursement for physicians consistently lags inflation. Studies are needed that describe reimbursement rates for lower extremity procedures. Our goal is to analyze the trends in Medicare reimbursement rates from 2010 to 2021 for both lower extremity amputation and salvage surgeries.Methods The Physician Fee Schedule Look-Up Tool of the Centers for Medicare and Medicaid Services was assessed and Current Procedural Terminology codes for common lower extremity procedures were collected. Average reimbursement rates from 2010 to 2021 were analyzed and adjusted for inflation. The rates of work-, facility-, and malpractice-related relative value units (RVUs) were also collected.Results We found an overall increase in Medicare reimbursement of 4.73% over the study period for lower extremity surgery. However, after adjusting for inflation, the average reimbursement decreased by 13.19%. The adjusted relative difference was calculated to be (−)18.31 and (−)11.34% for lower extremity amputation and salvage procedures, respectively. We also found that physician work-related RVUs decreased by 0.27%, while facility-related and malpractice-related RVUs increased.Conclusion Reimbursement for lower extremity amputation and salvage procedures has steadily declined from 2010 to 2021 after adjusting for inflation, with amputation procedures being devaluated at a greater rate than lower extremity salvage procedures. With the recent marked inflation, knowledge of these trends is crucial for surgeons, hospitals, and health care policymakers to ensure appropriate physician reimbursement.Level of Evidence IV (cross-sectional study).
Keywords: Medicare; lower extremity surgery; general; plastic surgery; surgeons